A study of a pressure analysis model for SRV fractured vertical wells in tight oil reservoir. (17th June 2019) - Zhu, Langtao; Liao, Xinwei; Zhao, Xiaoliang; Mu, Lingyu; Cheng, Xuyang
Tight matrix blocks and fractures normally have high stress-sensitivity. In addition, due to the tightness, unsteady cross-flow (UCF) often occurs between matrix and fractures. Those two factors can affect the shapes and characteristics of bottom hole pressure (BHP) and thereby the reliability of well test interpretation. In this study, a physical model of a fractured vertical well with stimulated reservoir volume (SRV) was developed for the purpose of pressure propagation simulation, based on micro-seismic data monitored at SRV fractured vertical wells in different typical tight oil reservoirs. Then a mathematical model was presented to describe BHP of SRV fractured vertical wells by considering stress sensitivity and UCF. Later, the proposed BHP analysis model was applied to a typical SRV fractured vertical well. The results reveal that compared to models without stress sensitivity and UCF, the proposed model can provide more accurate estimates of the inner fractured zone's radius and other relevant reservoir parameters. [Received: March 15, 2017; Accepted: July 17, 2017]